2019
DOI: 10.1093/mnras/stz1884
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and H i in ultra-diffuse galaxy UGC 2162

Abstract: ABSTRACT Our GMRT (Giant Metrewave Radio Telescope) H i observations of the ultra-diffuse galaxy (UDG) UGC 2162, projected ∼ 300 kpc from the centre of the M 77 group, reveal it to a have an extended H i disc ($R_{\rm H\,{\small I}}/R_{25}$ ∼ 3.3) with a moderate rotational velocity (Vrot ∼ 31 km s−1). This Vrotis in line with that of dwarf galaxies with similar H i mass. We estimate an Mdyn of ∼1.14 × 109 M⊙ within the galaxy’s $R_ \rm {H\,{\small I}}$ ∼ 5.2 kpc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Analysis of the DM content of six of the UDGs in the Leisman sample of isolated H i detected UDGs (Mancera Piña et al 2019Piña et al , 2020 indicates that those galaxies are baryon dominated within their R HI , see Figure 4 in Mancera Piña et al (2019), although their results are based on a limited number of bbarolo (Di Teodoro & Fraternali 2015) 3D kinematic tilted-ring disc model fits for each galaxy. A similar, although lower magnitude, departure from the BTFR was reported in Sengupta et al (2019) for the UDG, UGC 2162 also derived from bbarolo fitting. Confirmation of a baryon dominated population of UDGs has important implications for the origin of those UDGs.…”
Section: Dark Matter Halossupporting
confidence: 81%
See 1 more Smart Citation
“…Analysis of the DM content of six of the UDGs in the Leisman sample of isolated H i detected UDGs (Mancera Piña et al 2019Piña et al , 2020 indicates that those galaxies are baryon dominated within their R HI , see Figure 4 in Mancera Piña et al (2019), although their results are based on a limited number of bbarolo (Di Teodoro & Fraternali 2015) 3D kinematic tilted-ring disc model fits for each galaxy. A similar, although lower magnitude, departure from the BTFR was reported in Sengupta et al (2019) for the UDG, UGC 2162 also derived from bbarolo fitting. Confirmation of a baryon dominated population of UDGs has important implications for the origin of those UDGs.…”
Section: Dark Matter Halossupporting
confidence: 81%
“…To date only a few UDGs have been mapped in H i (e.g. Leisman et al 2017;Sengupta et al 2019;Mancera Piña et al 2019). Interestingly, several of these UDGs with resolved H i show an apparent departure from the McGaugh et al (2000) baryonic Tully Fisher relation (BTFR).…”
Section: Dark Matter Halosmentioning
confidence: 99%
“…In the "high-spin" model (Amorisco & Loeb 2016), a higher initial halo spin for a dwarf-like halo produces a galaxy with a large effective radius and hence low surface brightness. Again, current observations, in this case H I observations of gas-rich UDGs, provide conflicting results with some finding high-spin (Spekkens & Karunakaran 2018;Liao et al 2019) and others finding low-spin (Jones et al 2018;Sengupta et al 2019) field UDGs. In the high-spin UDGs, the baryons are less concentrated than in the low-spin analogs and so, in addition to the stars being more spread out, a lower star formation efficiency may also plausibly be responsible for the galaxy's low surface brightness.…”
Section: Introductionmentioning
confidence: 72%
“…These HI-dominated systems are often remnants of past tidal (or hydrodynamic) interactions and/or could be more extreme cousins of very low surface brightness galaxies such as the class of HI-rich tidal dwarf galaxies (Bournaud et al 2007;Lelli et al 2015;Lee-Waddell et al 2016;Leisman et al 2016;Sengupta et al 2017) and 'almostdark' galaxies (e.g. Leisman et al 2017;Sengupta et al 2019;Janowiecki et al 2019;Scott et al 2021). Galaxy evolution models have demonstrated that the majority of HI clouds without optical counterparts are likely the result of galaxy-galaxy interactions (e.g.…”
Section: Introductionmentioning
confidence: 99%